Konsep Arsitektur Rumah Adat Suku Osing di Desa Kemiren, Banyuwangi - Kriswikana Noor, I Made; Siwalatri, Ni Ketut Ayu; ., Widiastuti (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2021)
Osing Community of Kemiren Village, Gelagah District, Banyuwangi is an ethnic group of Java Island in Indonesia that still maintains and preserves its culture, especially of that pertains to its home. Osing’s traditional house has a unique concept that is different in comparison with traditional Javanese houses in general. This includes uniqueness in building orientation, spatial pattern, architectural forms, and the use of building materials. The purpose of this study is to conceptualize the architecture of Osing’s traditional house in terms of spatial patterns, forms, functions, structure, and building materials. This research uses qualitative research with an ethnographic approach. Study findings show that Osing traditional house is passed down from generation to generation. Its spatial layout has a cosmological orientation that rules a home should conform with a north-south axis forming a linear pattern and should not face a mountain. Home has 3 rooms, namely bale , jrumah , and pawon laid in a parallel and symmetrical spatial pattern. In this arrangement, jrumah is considered the center of the house as well as a private zone. In addition to this, a home is a representation of a binary concept - dark-light, male-female, public-private, left-right, and sacred-profane. Osing’s traditional house uses building materials that are locally available and adequately support its structure. The main considerations applied in selecting these materials are comfort and capacity to adapt to the surrounding environment. Keywords: traditional house, spatial pattern, form, and function, architectural concept, Osing ethnicity   Abstrak Suku Osing di Desa Kemiren, Kecamatan Gelagah, Banyuwangi merupakan suku yang masih tetap menjaga dan melestarikan adat istiadat dan budaya, yaitu pada rumah adatnya. Rumah adat Suku Osing memiliki konsep yang unik dan berbeda dari rumah adat Jawa pada umumnya, baik dalam orientasi bangunan, pola ruang, dan bentuk arsitektur, serta material bangunan. Tujuan penelitian ini adalah untuk menganalisis konsep arsitektur rumah adat yang ditinjau dari pola ruang, bentuk dan fungsi ruang, serta material dan struktur. Pada penelitian ini menggunakan metode kualitatif pendekatan etnografi. Hasil penelitian memperlihatkan bahwa rumah adat Suku Osing mampu diwariskan secara turun-temurun. Tata letak rumah adat memiliki orientasi kosmologis yaitu cenderung ke arah utara-selatan dan rumah tidak boleh menghadap gunung. Dilihat dari skala makro, pola permukiman Suku Osing tersusun dengan pola linier. Pola ruang utama memiliki 3 ruang dengan fungsi masing-masing, yaitu bale, jrumah , dan pawon yang terbentuk dari pola ruang sejajar dan simetris.  Jrumah merupakan sentral dan bersifat privat. Konsep ruang memperlihatkan unsur dualitas, yaitu gelap-terang, laki-laki-perempuan, publik-privat, kiri-kanan, dan sakral-profan. Material rumah adat merupakan material yang mudah didapati dan berada di sekitar desa dengan sistem struktur yang sederhana. Pemilihan material mengutamakan kenyamanan, dan adaptasi terhadap lingkungan sekitar. Kata kunci : rumah adat, pola ruang, bentuk dan fungsi, konsep arsitektur, Suku Osing